The Success of the Bakamla Patrol Ship Weapon In Creating Maritime Security In The North Natuna Sea - Yudhawira Bhaskara Sembiring; Desi Albert Mamahit; Budiman Djoko Said; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The Indonesian Coast Guard's use of firearms in the North Natuna Sea, an area designated as a high-priority zone by the Indonesian government due to high levels of traffic and maritime threats. In August 2020, the Indonesian Defense Minister authorized the Coast Guard to use 5.56 mm, 12.7 mm, and 30 mm caliber guns to secure the sea, which has raised questions about its potential impact on maritime security. The study examines the effectiveness of these weapons on Bakamla ships and whether they can incapacitate rather than kill the threat. Using qualitative research methods, including interviews and literature reviews, the study found that the Coast Guard is capable of using these weapons with adequate ammunition, but the 12.7 mm caliber firearm requires careful use due to its destructive power. The study suggests that the use of these firearms can improve maritime security in the North Natuna Sea, but only when used responsibly and with proper training